Analysis of Online Learning Process at SMP Muhammadiyah 5 Tulangan - Indah Nur Febriyanti; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
This study aims to find out a brief history of the history of Muhammadiyah education in Tulangan, Sidoarjo, learning strategies, analyzing the courageous learning process, supporting and inhibiting factors for teachers in carrying out learning during the Covid-19 pandemic. The Covid-19 pandemic has had a very big impact on education, especially in the learning process that was initially carried out directly but is now converted into courageous learning. Students are required to be accustomed to less effective courage. This research was conducted at SMP Muhammadiyah 5 Tulangan. This research used This type of research is a qualitative descriptive method. By taking sound recordings during the interview process. Learning strategies are carried out in order to achieve learning objectives which are expected to establish good communication between teachers, students and also guardians of students. As for some of the supporting factors for teachers in the learning process, namely the number of cellphones, quotas, and stable internet networks. And the inhibiting factor is not being able to meet face to face directly which makes students not focus on receiving online learning.